2015
DOI: 10.1093/asj/sju158
|View full text |Cite
|
Sign up to set email alerts
|

Nipple-Sparing Mastectomy via an Inframammary Fold Incision with Implant-Based Reconstruction in Patients with Prior Cosmetic Breast Surgery

Abstract: 4 Therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Nipple‐areola‐sparing mastectomy has the potential to offer a more esthetic result to patients and is a valuable approach for risk reduction and cancer treatment in certain patients . Recently, the rates of NSM performed have been increasing, much in line with the rate of cosmetic breast surgery …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nipple‐areola‐sparing mastectomy has the potential to offer a more esthetic result to patients and is a valuable approach for risk reduction and cancer treatment in certain patients . Recently, the rates of NSM performed have been increasing, much in line with the rate of cosmetic breast surgery …”
Section: Discussionmentioning
confidence: 99%
“…Dent et al recorded data on patients who underwent NSM after cosmetic breast surgery yet did not document incision patterns. Prior surgery resulted in significantly higher rates of mastectomy skin flap necrosis (31.7% vs 18.2%) and hematoma (9.8% vs 3.1%) . Jensen's group performed surgical delay on all their seven patients whom they felt were high risk for nipple necrosis: smokers, scars, etc No NAC complications were reported in patients using their staged approach …”
Section: Discussionmentioning
confidence: 99%
“…The IMF incision has the advantage of hiding the scar in a natural crease while providing sufficient exposure for resection. 16,17,31 This approach is particularly beneficial in patients who require nipple/NAC resection because it minimizes the scar burden and skin tension at the site of future reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…A description of this technique is given in Appendix 1. This obviates the need for use of electrocautery close to the skin flaps, which is thought to reduce soft tissue damage from the dissipation of thermal energy . Previous studies have shown no increase in post‐op complications compared to conventional electrocautery technique.…”
Section: Introductionmentioning
confidence: 99%